Development of Blog-Based Mathematics Learning Media Using Malay Islamic Context in Junior High School - Syutaridho, Syutaridho; Nizar, Harisman (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
The use of technology in learning is a big issue in the world of education. The need to pair technology with learning is a form of response to technological developments. One technology that can be used in learning is blog-based learning media.  This research aims to produce blog-based mathematics learning media with a Malay Islamic context in junior high schools that is valid and practical and has a potential effect on mathematical problem solving abilities. This type of research is design research, development study type, which involves students at junior high school level. This research data was obtained from observations, interviews, and tests. The conclusion of this research is to produce blog-based mathematics learning media with a Malay Islamic context in junior high schools that is valid and practical. The uniqueness of the blog media developed is that it uses a Malay Islamic context. Then the media developed has a potential effect on students' problem solving abilities with details of 20 students having problem solving abilities in the very high category, 19 students in the high category, 5 students in the moderate category, 4 students in the low category, and 2 students in the low category. students in the very low category. Then the average mathematical problem solving was 72.48 in the high category. By knowing the   development of this blog learning media, teachers and other researchers can develop blog-based mathematics learning media in other contexts that are close to students.\ Penggunanan teknologi dalam pembelajaran menjadi isu besar dalam dunia pendidikan. Keharusan menyandingkan teknologi dengan pembelajaran merupakan bentuk respon terhadap perkembangan teknologi. Salah satu dari teknologi yang dapat digunakan dalam pembelajaran adalah media pembelajaran berbasis blog. Penelitian ini bertujuan menghasilkan media pembelajaran matematika berbasis blog dengan Konteks Islam Melayu di SMP yang valid dan praktis serta memiliki efek potensial terhadap kemampuan pemecahan masalah matematis. Tipe penelitian ini adalah design research tipe development study yang melibatkan siswa pada level SMP. Data penelitian ini didapat dari hasil observasi, Wawancara dan Tes. Kesimpulan dari penelitian ini yaitu menghasilkan media pembelajaran matematika berbasis blog dengan konteks Islam Melayu di SMP yang valid dan praktis. Keunikan dari media blog yang dikembangkan adalah menggunakan konteks Islam Melayu. Kemudian media yang dikembangkan memiliki efek potensial terhadap kemampuan pemecahan masalah peserta didik dengan rincian 20 peserta didik memiliki kemampuan pemecahan masalah dengan kategori sangat tinggi, 19 peserta didik kategori tinggi, 5 peserta didik dengan kategori cukup, 4 peserta didik dengan kategori rendah, dan 2 peserta didik dengan kategori sangat rendah. Kemudian rata-rata pemecahan masalah matematis sebesar 72,48 dengan kategori tinggi. Dengan mengetahui pengembangan media pembelajaran blog ini, guru dan peneliti lain dapat mengembangkan media pembelajaran matematika berbasis blog pada konteks lain yang dekat dengan siswa.